Profiling Organizational Citizenship Behaviour (An Empirical Study of Public and Private Food Processing Industry) - Luxmi (Gyan Management Journal, 2011)
This study was designed to compare Organizational Citizenship Behaviour of the employees in public and Private sector organizations in Food Processing Industry, to see the association between subscales of organizational citizenship behaviour and to compare these dimensions of organizational citizenship behaviour vis-a-vis different psycho-demographic factors of the employees. The scope of the study was Public and Private sector organizations belonging to Punjab, Haryana and Chandigarh in Food Processing Industry. The sample comprised of 196 respondents drawn from three public sector organizations, and six private sector organizations. Comparisons made on the basis of hierarchical levels and other psycho-demographic factors make the study comprehensive. The results revealed a very significant but weak positive correlation between three subscales of Organisational Citizenship Behaviours. Almost all other null hypotheses concerning level of Organisational Citizenship Behaviours vis-a-vis failed to be rejected unlike previous similar studies.